Answer:
Please check the explanation.
Step-by-step explanation:
Let the coordinates of the point F be (x, y).
When a point F(x, y) is reflected over the x-axis, the x-coordinate of the point F remains the same, and the y-coordinate of the point reverses the sign.
Thus, the rule of reflection over the x-axis:
F(x, y) → F'(x, -y)
Here,
F'(x, -y) would be coordinates of point F after the reflection over the x-axis.
Let say, the point F(1, 2).
The coordinate of the point F after the reflection over the x-axis would be:
F(1, 2) → F'(1, -2)
Thus, F'(1, -2) would be the coordinates of point F after the reflection over the x-axis.
That equal 1 because they are the same
Answer:
x^2 + 5n = 4mx
=> x^2 - 4mx + 5n = 0
D=0 (since one root then roots are equal)
b^2-4ac = 0
(-4m)^2 - 4(1)(5n) = 0
16m^2 - 20n = 0
16m^2 = 20n
8m^2 = 10n
4m^2 = 5n
hope it helps.......
Answer:
right angle?
Step-by-step explanation:
Joint Frequency because of the fact that it "joins" one number from the column(up and down) and one from the row(side-by-side), hence the two-way table.